Electrically conductive adhesives, thermally conductive adhesives and UV adhesives in data extraction forensics. (June 2017) - Heckmann, Thibaut; Souvignet, Thomas; Naccache, David
Abstract: Recent publications underline the interest of using polymers in microelectronics (Li and Wong, 2006a; Cui et al., 2014). Polymers are the ideal interconnect alternative to solder materials containing lead. Electrically Conductive Adhesives [ECAs] (Li and Wong, 2006b), Thermally Conductive Adhesives (TCAs) (Felba et al., 2011) and UV Adhesives (UVAs) (Asif et al., 2005) mainly consist of a polymeric resin (epoxy, silicon, polyurethane or polyimide) that provides physical and mechanical properties such as adhesion, mechanical strength while containing metal fillers (silver, gold, nickel or copper) that conduct electricity (Luo et al., 2016). Currently it is possible to find really cheap polymeric resin. Using these resins for digital forensic purposes is the focus of this paper, that we demonstrate in a hardware reverse engineering prototype case study. When considering new mobile devices, such as secure phones, it is often necessary to spy communication and perform numerous tests on the memory (e.g. by changing some bytes) to understand or modify the implemented security mechanisms (manipulate system time, locate password hashes, observe artefacts of implemented security algorithms, etc.). Traditional techniques use either laser attacks/probing (chip on) or soldering/read/re-soldering (chip off/on) (Heckmann et al., 2016, Jongh, 2014). These two techniques are unsuitable for repeated operations requiring many readings/changes/injections. This paper describes a concrete case study using adhesive properties complementary to chip on and chip off methods. We present the steps using different properties of adhesives (ECA, TCA, UVA) that we will lead to the realisation of a prototype particularly suitable for the repeating of the read phases/changes/injections necessary for reverse engineering secure mobile devices.